Penerapan Sistem Proteksi Arus Bocor pada Instalasi Listrik Rumah Tinggal - Kilis, Billy; Mamahit, Calvin (Department of Electrical Engineering Education, Faculty of Engineering, State University of Manado, 2021)
This study focuses specifically on household needs because electricity is an inseparable part of daily needs The problems identified are how the protection system uses the earth leakage circuit breaker ELCB model for residential installations and how to apply it in residential homes quickly and straightforwardly In the current protection system the built system must work in the range of lt; 30 mA according to the general requirements of electrical installations in Indonesian abbreviated: PUIL when the muscles cannot release the conductor or are dangerous The test results of ELCB enhancements can be applied in residential homes and thus can be helpful for the community in avoiding short circuits and fires The conclusion is that the resistance measurement for the 21 participants went well and the average resistance value was 3665 k Thus the tool on the simulator works according to the operation according to PUIL < strong>< p> Abstrak < strong>Kajian ini lebih memfokuskan secara khusus untuk kepentingan rumah tangga karena listrik menjadi hal yang tak terpisahkan dalam kebutuhan sehari hari Masalah yang dapat diidentifikasi adalah bagaimana sistem proteksi menggunakan model earth leakage circuit breaker ELCB untuk instalasi rumah tinggal dan bagaimana cara penerapannya di rumah tinggal secara mudah dan sederhana Pada sistem proteksi arus sistem yang dibangun harus bekerja pada rentang lt; 30 mA menurut persyaratan umum instalasi listrik PUIL merupakan saat dimana otot tidak sanggup melepaskan penghantar atau berbahaya Hasil pengujian piranti tambahan ELCB dapat diterapkan di rumah tinggal dan dengan demikian dapat berguna bagi masyarakat dalam menghindari hubung singkat dan kebakaran Kesimpulan pengukuran tahanan untuk para partisipan berjumlah 21 orang berjalan dengan baik dan diperoleh nilai tahanan rata rata 3665 k Dengan demikian alat pada simulator bekerja sesuai dengan operasi menurut PUIL < strong>< p>